2005
DOI: 10.1177/216507990505300311
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick Injuries in the United States: Epidemiologic, Economic, and Quality of Life Issues

Abstract: eedlestick injuries pose a recognized occupational hazard to health care workers. The first case of occupationally acquired human immunodeficiency virus (HIV) infection was reported in 1984 and highlighted the risk of occupational exposure to HIV and hepatitis (Anonymous, 1984). During the past decade, the Occupational Safety and Health Administration (OSHA) of the U.S. Department of Labor has led government efforts to decrease the risk of exposure through needlestick injuries. In 1991, OSHA promulgated the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(99 citation statements)
references
References 63 publications
2
96
0
1
Order By: Relevance
“…To estimate medical costs-per-needlestick prior to treatment for infection we first calculated a mean from eight studies (six from a published literature review 5 and one each from WC Lee et al 6 and Shah et al 7 ) and second, combined the mean with information on source-patients from Orenstein et al 9 to generate six separate estimates. We used cost data from Orenstein et al 9 studies in the JM Lee et al 5 review and since it has the most detail on cost-per-disease and source-patient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate medical costs-per-needlestick prior to treatment for infection we first calculated a mean from eight studies (six from a published literature review 5 and one each from WC Lee et al 6 and Shah et al 7 ) and second, combined the mean with information on source-patients from Orenstein et al 9 to generate six separate estimates. We used cost data from Orenstein et al 9 studies in the JM Lee et al 5 review and since it has the most detail on cost-per-disease and source-patient.…”
Section: Methodsmentioning
confidence: 99%
“…Hospitals, however, accounted for only 40.1% of employment within the healthcare sector in 2004 4 . The most thorough published literature review includes ranges for perperson costs of needlesticks, but our literature search found only one estimate of national total costs 5,6 . The national estimate by Lee et al 6 assesses immediate testing and related costs but gives less attention to long-term costs of treatment of subsequent infections.…”
Section: Introductionmentioning
confidence: 99%
“…Although the risk of HIV infection is generally lower than the risk of infection by HBV or HCV, the occupational acquisition of HIV represents a serious consequence of needlestick injuries (Prüss-Üstün et al 2005). In addition, HCWs suVer from signiWcant anxiety and emotional distress following a needlestick injury (Lee et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that short-term follow-up medical treatments range from $50 to $3800 in the United States, and long-term treatment associated with HIV, HBV, or HCV seroconversion can reach hundreds of thousands of US dollars. 11 Unreported sharp injuries and blood/body fluid exposures, estimated to range from 40% to 80%, 9,11,12 present a 2-fold dilemma according to Wilburn 12 : 1) Injured health care workers often do not receive timely post-HIV exposure prophylaxis that may be up to 80% effective against HIV infection; and 2) the magnitude of the problem remains unknown and challenges the implementation of appropriate interventions, such as the implementation of safe work practices and the development of improved medical devices with features of sharp injury prevention.…”
mentioning
confidence: 97%